Sequences adjacent to oriP improve the persistence of Epstein-Barr virus-based episomes in B cells. - White, R; Wade-Martins, R; James, MR (2001)
Epstein-Barr virus (EBV) oriP and the EBV nuclear antigen 1 (EBNA-1) protein allow persistence of EBV-based episomes. A nuclear matrix attachment region (MAR) spans oriP and the adjacent region of the EBV genome containing the EBV-expressed RNAs. Here, we show that episomes with the MAR are retained significantly more efficiently in EBV-positive B cells than episomes containing oriP alone.